IMF Research Bulletin, June 2008. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2008)
IMF research summaries on Latin America's external linkages (by Shaun Roache) and on reaping the benefits of structural reforms (by Stephen Tokarick); regional study on the Eastern Caribbean Currency Union (by Paul Cashin and Evridiki Tsounta); listing of visiting scholars at the IMF during March-April 2008; listing of contents of Vol. 55 No. 2 of IMF Staff Papers; listing of recent IMF Working Papers; listing of recent external publications by IMF staff; and a call for papers for the Jacques Polak Ninth Annual Research Conference.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet